1990
DOI: 10.1111/j.1365-2796.1990.tb00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated fibrinogen and plasminogen activator inhibitor (PAI‐1) in hypertension are related to metabolic risk factors for cardiovascular disease

Abstract: The relationship between hypertension, glucose metabolism, fibrinogen and plasminogen activator inhibitor of endothelial cell type (PAI-1) was studied under conditions in which the influence of obesity and adipose tissue distribution (waist/hip ratio) were controlled. Twenty-two non-obese, middle-aged men with normal blood pressure (n = 11) and untreated mild hypertension (n = 11), respectively, participated in the study. Cholesterol, triglyceride and insulin levels were higher in hypertensive men than in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
117
1
5

Year Published

1994
1994
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(138 citation statements)
references
References 21 publications
15
117
1
5
Order By: Relevance
“…A significant correlation among hypertensives between PAI-1 and the level was noted between absolute levels of vWF and both of both insulin and lipoprotein and a negative systolic and diastolic BP among patients with either relationship with the rate of glucose disposal have controlled or uncontrolled hypertension in the been shown. 59,62,73 In a study of non-obese hypertenabsence of vascular disease or risk factors. This, sive men, treatment with metformin lowered BP and coupled with the finding that concurrent vascular tended to increase the fibrinolytic activity of the disease or risk factors were not associated with any subjects.…”
Section: Red Cell Aggregationmentioning
confidence: 99%
“…A significant correlation among hypertensives between PAI-1 and the level was noted between absolute levels of vWF and both of both insulin and lipoprotein and a negative systolic and diastolic BP among patients with either relationship with the rate of glucose disposal have controlled or uncontrolled hypertension in the been shown. 59,62,73 In a study of non-obese hypertenabsence of vascular disease or risk factors. This, sive men, treatment with metformin lowered BP and coupled with the finding that concurrent vascular tended to increase the fibrinolytic activity of the disease or risk factors were not associated with any subjects.…”
Section: Red Cell Aggregationmentioning
confidence: 99%
“…[12][13][14][15] The metabolic background of this strong relationship between fibrinogen levels and cardiovascular risk has not been fully elucidated, although a number of studies showed significant associations between fibrinogen and several other cardiovascular and hemostatic variables. [16][17][18][19][20][21][22][23] Unfortunately, measurements for fibrinogen were poorly standardized for some time, thereby limiting its wide adoption in the clinical setting. Currently accepted assays for fibrinogen are widely available and have acceptable coefficients of variation.…”
mentioning
confidence: 99%
“…[73] These changes suggest impaired fibrinolysis and a procoagulant hemostatic blood profile. Experimental studies indicate that the spontaneous dissolution of a cerebral embolus is significantly lower in hypertensive compared with normotensive rats.…”
Section: Hypertensionmentioning
confidence: 99%